Knowledge and Practice towards Hygiene and Sanitation Amongst Residents of Dhankuta Municipality - Sah, Ram Bilakshan; Bhattarai, S; Baral, D D; Pokharel, P K (Health Renaissance, 2015)
Background: Poor hygiene practices and inadequate sanitary conditions play major roles in the increased burden of communicable diseases within developing countries. Objectives: To know knowledge and practice regarding hygiene and sanitation of households and to find out the hygienic practices with selected variables. Methods: This cross-sectional study was conducted from 30th April to 13th May 2012 in Dhankuta Municipality where 300 households were taken as subjects. Among 9 wards, 3 wards were randomly selected and equal number of households (100) from each ward was selected on the basis of simple random sampling. Semi-structured questionnaire was used and face to face interview was conducted. Chi-square test was applied to find out the hygienic practices with selected variables. Results: Most of respondents believed that hand washing reduces diseases (71.3%). They knew that diarrhoea is spread by dirty environment (55.7%) and drinking unsafe water (46.3%) and unhygienic food (43.3%). Majority of respondents (95.3%) washing hands with soap and water after defecation. Almost (30%) respondents used burning as a management of solid waste. The ladies were found to have better hygienic practices (92%) than gents (61.6%) and Brahmin/Chhetri (70%) were more hygienic than other ethnic groups. Conclusion: The knowledge and practice on hygiene and sanitation among the households of Dhankuta municipality was found to be fair. DOI: http://dx.doi.org/10.3126/hren.v12i1.11985 Health Renaissance 2014;12(1):44-48